Implementasi Konsep Dan Praktik Filantropi Islam Di Indonesia - Muslikhah, Khusnul; Kurniawan, Naufal (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2023)
The research objective is to describe the concept and practice of Islamic philanthropy in Indonesia. Qualitative research methods with a library study approach. Data collection techniques with documentation studies sourced from scientific articles and books. The results of the Pustaka study show: among Indonesian Muslims, philanthropic activities have increased in various sectors, both in the political bureaucracy, law, and social and cultural institutions of society. This can be observed from the increasing efforts to raise public funds originating from zakat and alms. The concept and practice of Islamic philanthropy in the contribution of philanthropic activities to improve the economy and the welfare of society reveal that philanthropic activities in Indonesia have been implemented in various forms such as zakat, infaq, and alms and its practice in the Baitul Mal wat Tamwil company and the National Amil Zakat Agency.